The minors as victims and offenders in sex crimes - Corrales Pampillo, Marianela (2021)
Thirty years after the approval of the Convention on the Rights of the Child, the legal status of children, based on the paradigm of comprehensive protection, continues to present challenges that seek to make effective the human rights inherent to all children and adolescents. From the principle of progressive autonomy of minors, the gradual exercise of rights is recognized. Among these we have sexual rights, demanding control and protection by the State to avoid victimization processes. The reduction of the beginning of criminalresponsibility as opposed to the greater protection of children, through the criminalization of conducts, may generate normative incongruities, whose solution may involve the relaxation of procedural guaranteesor impunity of serious conducts.